Improved throughput bit-serial multiplier for GF(2m) fields - Michail, Harris; Selimis, George N.; Fournaris, Apostolos P. (My University, 2009)
High throughput is a crucial factor in bit-serial GF(2m) fields multiplication for a variety of different applications including cryptography, error coding detection and computer algebra. The throughput of a multiplier is dependent on the required number of clock cycles to reach a result and its critical path delay. However, most bit-serial GF(2m) multipliers do not manage to reduce the required number of clock cycles below the threshold of m clock cycles without increasing dramatically their critical path delay. This increase is more evident if a multiplier is designed to be versatile. In this article, a new versatile bit-serial MSB multiplier for GF(2m) fields is proposed that achieves a 50% increase on average in throughput when compared to other designs, with a very small increase in its critical path delay. This is achieved by an average 33.4% reduction in the required number of clock cycles below m. The proposed design can handle arbitrary bit-lengths upper bounded by m and is suitable for applications where the field order may vary.
Keywords: Cryptography; Hardware; Multiplication